The Role of Transportation and Accessibility in the Development of Sustainable Tourism Destinations - Daffa Mufid Hakim; Alya Putri Ramadhani; Nathan William Pratama (Lembaga Penelitian dan Pendidikan, 2026)
Transportation and accessibility are fundamental components in the development of sustainable tourism destinations. Efficient transportation systems facilitate tourist mobility, improve destination competitiveness, and support regional economic growth while minimizing environmental impacts. This study aims to examine the role of transportation and accessibility in fostering sustainable tourism development through a comprehensive literature-based analysis. A qualitative approach employing a systematic review of recent scientific publications was utilized to explore the relationship between transportation infrastructure, accessibility, and tourism sustainability. The findings indicate that well-integrated transportation systems significantly enhance tourist satisfaction, destination attractiveness, and local economic opportunities. Furthermore, sustainable transportation solutions such as public transit, multimodal transportation networks, non-motorized mobility, and accessible infrastructure contribute to environmental conservation and social inclusivity. Accessibility was found to be a critical factor influencing destination competitiveness, visitor experience, and the participation of diverse groups, including people with disabilities. The study also reveals that transportation planning integrated with sustainability principles can reduce congestion, carbon emissions, and environmental degradation in tourism destinations. Therefore, transportation and accessibility should be considered strategic elements in tourism policy and destination management. The study contributes to the growing body of knowledge on sustainable tourism by highlighting the importance of transportation systems in achieving long-term economic, environmental, and social sustainability.